Restoration of endometrial receptivity and reproductive function in infertile women with excess body weightand complex non-atypical endometrial hyperplasia - Nosenko, O.; Yurchenko, S. (Journal of Education, Health and Sport, 2022)
To date, there are several approaches to the treatment of endometrial hyperplasia, but it is quite unclear which approach provides a higher clinical response with a lower recurrence rate, in addition to preservation and restoration of fertility in infertile women with complex non-atypical endometrial hyperplasia (NEH) and excess body weight. The purpose of the study was to evaluate the effectiveness of the restoration of reproductive function in patients with infertility, complex NEH and with excess body weight according to the proposed method. Material and methods. 74 women of reproductive age with complex NEH, infertility and excess body weight were under observation, of which 34 patients of the main group after hysteroscopic resection of the lesion at the first stage of treatment, at the second stage of treatment received gonadotropin-releasing hormone agonists (aGnRH) and adjuvant therapy with drugs indole-3-carbinol, metformin, fenofibrate for three months, and then at the third stage of treatment dydrogesterone, metformin, a vitamin-mineral complex that included myo-inositol, banaba leaves, extract of 1% corosolic acid, vitamin D3, methylfolate-quatrafolic, chromium for 6 months. 40 patients of the control group after hysteroscopic resection of the lesion at the first stage of treatment were prescribed aGnRH for 3 months in the second stage of treatment, then methylfolate-mvatrafolic for 6 months. Anthropometric data, echometric and morphofunctional characteristics of the endometrium during the expected window of implantation, hormonal profile and levels of peripheral blood lipokines in the dynamics of treatment were studied. Reproductive results were evaluated within a year after the end of treatment. The results. Treatment of complex NEH in the main group led, compared to the control group, to a decrease in body mass index, improvement in echometric and morphofunctional characteristics of the endometrium, its receptivity during the expected window of implantation, hormonal profile and lipokines level in peripheral blood, a decrease in insulin resistance, and an increase in the frequency of pregnancy. Conclusion. The proposed scheme for the treatment of complex NEH in infertile women with excess body weight allowed to improve their reproductive results, is effective and can be recommended for implementation in wide clinical practice.